The Doctor Blake mysteries. Season three [videorecording (DVD)] - McLachlan, Craig, 1965-; Garner, Nadine; Cousins, Charlie (BBC Worldwide Ltd., 2016)
The continuing story of Dr. Lucien Blake as he practices medicine and investigates murder in 1950s rural Australia.